2006
DOI: 10.1111/j.1399-6576.2006.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

The former preterm infant and risk of post‐operative apnoea: recommendations for management

Abstract: The preterm infant presenting for anaesthesia during the first 6 months of life is a major anaesthetic challenge. One of the most serious post-operative complications is apnoea with or without bradycardia. For this review, we conducted a search of the current literature in order to formulate a set of evidence-based clinical guidelines to help clinicians in the management of the former preterm infant to avoid post-operative apnoea. Only a small number of patients have been enrolled into prospective, randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 47 publications
1
56
0
7
Order By: Relevance
“…Days on mechanical ventilation continuous positive airway pressure are indicators, too (21). All of these conditions affect the postoperative outcome of the babies (22). In our study, only anesthetic technique was found to have an effect on the need for postoperative mechanical ventilation.…”
Section: Discussionmentioning
confidence: 67%
“…Days on mechanical ventilation continuous positive airway pressure are indicators, too (21). All of these conditions affect the postoperative outcome of the babies (22). In our study, only anesthetic technique was found to have an effect on the need for postoperative mechanical ventilation.…”
Section: Discussionmentioning
confidence: 67%
“…Em consonância com nossos achados demonstrando que displasia broncopulmonar e leucomalácia periventricular foram os únicos fatores de risco preditores de desfecho desfavorável após raquianestesia, um estudo de revisão relatou que a apneia pós-operatória em recém-nascidos pré-termo esteve associada a displasia broncopulmonar, episódios de apneia no ambiente doméstico, doença neurológica e anemia 9 .…”
Section: Discussionunclassified
“…No entanto, orientações baseadas em evidências concluíram que recém-nascidos com história de apneia contínua, anemia, doença neurológica ou displasia broncopulmonar podem estar predispostos a apneia pós-operatória significativa até mesmo após raquianestesia, e devem ser considerados de risco 9 . Não foram investigadas outras complicações como alimentação tardia e hospitalização prolongada em recém-nascidos pré-termo submetidos a raquianestesia.…”
Section: Introductionunclassified
“…A recent meta-analysis concluded that former preterm infants undergoing general anesthesia who are less than 46 weeks' corrected gestational age should be observed for at least 12 hours postoperatively and that those who are between 46 and 60 weeks' corrected gestational age should receive more individualized care on the basis of the presence or absence of associated comorbidities. 40 To reduce the incidence of postoperative apnea, spinal, rather than general, anesthesia has been used for inguinal hernia repair in preterm infants. [41][42][43] Although some studies have been encouraging, none have been adequately powered.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 99%